Estimation of radiation doses of population residing nearby area of uranium ore mining and processing in Kazakhstan by tooth enamel EPR spectroscopy - Kassym Zhumadilov; Alexander Ivannikov; Murat Kassymzhanov; Assel Bagramova; Issa Zhantore; Sarsenova Samal; Valeriy Stepanenko; Artem Khailov; Masaharu Hoshi (Environmental Challenges)
To assess the impact of natural and technogenic radioactivity in uranium mining enterprises on the population, an investigation by the tooth enamel EPR (Electron Paramagnetic Resonance) dosimetry method was conducted for a group of the population living in the Stepnogorsk city (North Kazakhstan) placed near a uranium mining plant. Accumulated radiation EPR doses in enamel were assessed for 96 teeth samples.From the measured values of EPR doses and the age of tooth enamel since its formation, the individual annual EPR dose rates (DR) were determined with average value of 1.75 ± 0.46 mGy/year corresponding to the hourly DR of 0.20 ± 0.05 µGy/hour (here and below after ± sign the error of the mean is shown). Data on the individual DR were analyzed for samples collected for population of different parts of Stepnogorsk (microdistricts). These data were compared with ambient dose equivalent rate (ADER) of gamma radiation measured by the conventional instrumental dosimetry. No significant differences in DR and ADER between microdistricts were found. The average ADER through the microdistricts of Stepnogorsk was 0.23 ± 0.01 µGy/hour (corresponding to 2.0 ± 0.1 mGy/year), which is consistent with the average DR measured by EPR.For some tooth donors significantly higher individual EPR doses and DR, exceeding up to several times the bulk level for the investigated group of population were obtained. These high values may be result of local increased radiation level caused by the wastes of uranium mining enterprises.